2011
DOI: 10.1016/j.tvjl.2011.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Humoral and cellular immune responses in dogs with inapparent natural Leishmania infantum infection

Abstract: Molecular analysis, serology and immunophenotyping for T lymphocytes and their subsets, B lymphocytes and monocytes were performed on dogs naturally infected with Leishmania infantum. Animals were categorised as asymptomatic dogs I (AD-I), with negative serology and positive molecular results, and asymptomatic dogs II (AD-II), with positive serology and positive molecular results, and these were compared to symptomatic dogs (SD) and control dogs (CD). AD-I exhibited immunophenotypic features similar to those o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
45
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 36 publications
6
45
1
1
Order By: Relevance
“…However, it is worth noting that despite a report of two dogs infected with Leishmania (L.) amazonensis in the municipality of Araçatuba, no cases of human disease nor the natural vector of this parasite species has been described in this region to date [17]. The immunohistochemical quantitative studies in lymph nodes or in spleens did not show significant differences ( P  = 0.2471 and P  = 0.5158, respectively) between the clinical groups, supporting the idea that our infected asymptomatic dogs could be in the pre-patent period of infection, as reported by Coura-Vital et al [16]. Figure 1A shows the number of parasites/mm 2 in the popliteal lymph nodes and spleens of symptomatic and asymptomatic dogs.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…However, it is worth noting that despite a report of two dogs infected with Leishmania (L.) amazonensis in the municipality of Araçatuba, no cases of human disease nor the natural vector of this parasite species has been described in this region to date [17]. The immunohistochemical quantitative studies in lymph nodes or in spleens did not show significant differences ( P  = 0.2471 and P  = 0.5158, respectively) between the clinical groups, supporting the idea that our infected asymptomatic dogs could be in the pre-patent period of infection, as reported by Coura-Vital et al [16]. Figure 1A shows the number of parasites/mm 2 in the popliteal lymph nodes and spleens of symptomatic and asymptomatic dogs.…”
Section: Resultssupporting
confidence: 83%
“…Thus, transversal studies related to natural infection in dogs can generate controversial results, especially when animals are sorted in clinical groups, since asymptomatic clinical status can represent a resistance pole, but also an early phase of infection or a pre-patent disease period [15]. Two populations of asymptomatic dogs in endemic areas has been characterized: one seronegative, but with positive molecular detection of L. (L.) infantum chagasi , and another with positive serology and molecular results for the parasite, suggesting that asymptomatic dogs have a dichotomous infection spectrum that can influence humoral and cellular immunological status during CVL infection [16]. …”
Section: Resultsmentioning
confidence: 99%
“…The difference between IFN-γ and L-10 explained the differences in parasite load between organs. A recent study carried out by Coura-Vital and co-workers [34], showed that asymptomatic dogs had a higher frequency of CD4 and CD8 T cells, these cells are the main producer of IFN-γ and TNF-α, which may lead to parasite control and maintenance of asymptomatic status. …”
Section: Discussionmentioning
confidence: 99%
“…Such phenomena are relatively common during Leishmania infection and may be related to the chronic phase of the disease (22,23).…”
Section: Infantum Upregulates Tlr9 Expression During Infectionmentioning
confidence: 99%